The Variuous Packaging Effects of Loker Telun Berasap Chili Damage During Storage - Salvia, Eva; Izhar, Lutfi; Nofriati, Desy (Department of Technology of Agricultural product (THP) Jambi University, 2020)
General characteristics of fresh horticultural products like chili, is easily get damaged after harvest. The chili declining quality and loss after harvesting occur due to ongoing respiration process. Hence, the chilies become wither or rot. This damage happens due to physical, microbiological, and physiological influences. Physical damage and yield loss can be caused by packaging uses during storage. The study aimed to determine the effect of packaging use type for Locker Telun Berasap chillies on the weight loss and damage during storage. The treatments were the commonly community packaging use types which consists of: a) polyethylene plastic (PE), b) paper and c) banana leaf. Each treatment was performed two replications and stored at room temperature. Observation parameters during storage were weight loss, and physical, physiological, microbiological damages. The lowest weight loss percentage for 12 days’ storage by PE packaging was 45.5%. The total damage was 30% lower compared to paper and banana leaf packaging. Optimal freshness can be achieved until the 8th day of storage with physical damage only 1.03% on PE packaging. The results of the study showed that the dominant microbiological damage was found in the banana leaf packaging treatment.